2000
DOI: 10.1046/j.1526-4610.2000.00016.x
|View full text |Cite
|
Sign up to set email alerts
|

Life Event Stress and Headache Frequency Revisited

Abstract: Life stress is found to be related to headache frequency in some studies, but not others. Research designs that find a relationship between the two tend to evaluate young subjects and employ large sample sizes. The purpose of this study was to evaluate the relationship between headache frequency and life stress, while considering gender and age differences that may be present in the relationship. In addition, as depression or presence of headache at the time of assessment may influence the report of headache f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0
1

Year Published

2003
2003
2016
2016

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 30 publications
2
23
0
1
Order By: Relevance
“…Stress, a commonly recognized trigger of migraine (Passchier, 1994;Reynolds and Hovanitz, 2000), may also initiate or intensify attacks, perhaps by acting on an unstable pain control system (Lance, 1993). In particular, stimulation from higher brain centres, such as the cortex or hypothalamus during stress or emotion, or excessive afferent input from the special senses or cranial vessels, may compromise the pain control system in individuals vulnerable to migraine.…”
Section: Migraine Triggersmentioning
confidence: 99%
“…Stress, a commonly recognized trigger of migraine (Passchier, 1994;Reynolds and Hovanitz, 2000), may also initiate or intensify attacks, perhaps by acting on an unstable pain control system (Lance, 1993). In particular, stimulation from higher brain centres, such as the cortex or hypothalamus during stress or emotion, or excessive afferent input from the special senses or cranial vessels, may compromise the pain control system in individuals vulnerable to migraine.…”
Section: Migraine Triggersmentioning
confidence: 99%
“…Both for men and women, sickness absence has been found to be a more powerful predictor of all-cause mortality than established self-reported health measures and available objective measures of specific physical illnesses and medical conditions (31), as well as a strong predictor of specific causes of death, such as cardiovascular disease, cancer, alcohol-related causes, and suicide (23), and a risk marker for future disability retirement (32). Observational studies have shown an increase in the risk of health problems after stressful events, including acute infections (2,3), headache (33), mental disorders (4,6), and asthma (5). All of these problems are common causes of sickness absence (34).…”
Section: J Vahtera Et Almentioning
confidence: 99%
“…A study by Reynolds and Hovanitz [15] found a mild correlation between the occurrence of NLEs and the frequency of headaches, which was no longer significant after adjustment for depression diagnosis. There was no separate analysis focusing on the migraine subgroup in that study.…”
Section: Introductionmentioning
confidence: 99%